Diversity of black pepper plant (Piper nigrum) in Bangka Island (Indonesia) based on agro-morphological characters - Gigih Ibnu Prayoga; Ropalia Ropalia; Sitti Nurul Aini; Eries Dyah Mustikarini; Yuniar Rosalin (Society for Indonesian Biodiversity, 2020)
Abstract. Prayoga GP, Aini SN, Mustikarini, ED, Rosalin Y. 2020. Diversity of black pepper plant (Piper nigrum L.) in Bangka Island (Indonesia) based on agro-morphological characters. Biodiversitas 21: 652-660. Black pepper (Piper nigrum L.) production in Bangka Belitung Islands Province continued to decrease in 2014-2017. Efforts to increase black pepper production was carried out by providing superior varieties that began with an increase in the genetic diversity of black pepper plants. Increasing the genetic diversity of black pepper can be done through black pepper germplasm exploration activities followed by characterization. The research aimed to obtain the agro-morphological characteristics of black pepper plants in Bangka island. Exploration was carried out by survey method in four regencies in Bangka Island. The research method used a survey method with convenience sampling technique. Observation of agro-morphological characters was carried out in accordance with the descriptor for black pepper from IPGRI (1995). The results of exploration of black pepper plants in Bangka Island have found 9 accessions of black pepper plants, consisting of 5 cultivars were Lampung Daun Lebar (LDL), Lampung Daun Kecil (LDK), Chunuk, and Jambi and 4 landraces namely Bogor, Peremis, Keriwil, and Merapin Daun Kecil (MDK). There were morphological differences in 9 accessions of black pepper plants, namely leaf lamina shape, leaf vein, leaf margin, lateral branch habit, leaf base shape, ripe fruit color, hanging vines, ground vines, and stem shape. Agro-morphological relationship of 9 accessions of black pepper plants can be divided into 5 clusters at a 50% similarity level. Based on this study, black pepper breeding program on Bangka Island could be done accessions of Peremis, Bogor, Nyelungkup, and Jambi as genetic sources. Furthermore, selection would be better to use length of petiole, length of stem segment, fruit size, percentage of perfect fruit, weight of 1000 fruits, and the weight of 1000 dried seeds as the selection criteria.